Wanna try something crazy? - Tan, Ying Jian (Nanyang Technological University, 2023)
Wanna Try Something Crazy? is a 3D animated short film project that was crafted over two semesters by a talented team of four: Chester Chia Wei-Ze, Tan Ying Jian, Charmaine Tee and Jerome Tan Zhi Rong. The film showcases keyframe animation with an artistic, painting-inspired aesthetic, using flat, hand-painted backgrounds projected onto 3D-modelled environments. Visual effects are created using both frame-by-frame 2D painted effects and motion graphics. This horror film, set in Singapore, ingeniously blends elements of black comedy to deliver a unique and thrilling cinematic experience. The story follows a drunken man who invites a girl to his home for a romantic evening. But when the girl whispers, "Wanna Try Something Crazy?" into his ear, the night takes a dark turn. The experience intensifies as the girl undergoes a fictional ritual, loosely inspired by Taoist Tengki possession, transforming into the Huli jing (fox spirit). While the film was a group accomplishment, this report will specifically focus on my personal contributions to the project, from pre-production to post-production. I will also conclude the report with a reflection of my expectations compared to the final outcome of the project.